Efisiensi Kinerja Aparatur Sipil Negara dalam Sistem Work From Home - Norma Parulian Saragi Napitu; Humaizi Humaizi; Budi Hartono (Universitas Medan Area, 2021)
In order to minimize the spread of the new type of corona virus or SARS-CoV-2 which causes covid-19, people are asked to work, study and worship from home. face-to-face activities to be postponed or canceled. work from home has the same obligations and responsibilities as working from the office. work from home has challenges and obstacles that are not easy, because not all sectors of work can be done from home. The research objective was to determine and analyze the efficiency of performance and to determine the factors inhibiting the efficiency of the performance of the State Civil Apparatus in the Work from Home system in the Regional Office VI of the Medan State Civil Service Agency. with qualitative methods, data analysis techniques using descriptive research. The results showed that during WFH the cost of office expenses was reduced by 40% each month, the employees who are obliged to be in WFH are those who use public transportation and are over 50 years old, but it does not rule out the possibility that the age below 50 can still be in WFH, sick condition. Inhibiting factors in implementing WFH are the unavailability of facilities and infrastructure such as laptops / computers, printers and internet data packages, interference from family members, procrastinating work, prioritizing work at home compared to office work. It is recommended that employees during WFH create a special room, list of jobs, time limits, and communicate regularly with superiors.